Chronic malnutrition in the Ucayali Region: an attempt to life - Diaz Encinas, Alida Isidora (2010)
The objetive of this study was to analyze the levels and trends of chronic malnutrition in the Ucayali region through statistics of 1996 information, 2000 and 2007-2008 of ENDES, Census of student’s size and the 2007 Census (Pattern OMS). The results were dramatic differences between rural districts away from the urban area of Coronel Portillo, for example, Calleria 19.5% versus Tahuania 75.4%.